A non-ordinary state-based peridynamics formulation for thermoplastic fracture - Amani, J.; Oterkus, E.; Areias, P.; Zi, G.; Nguyen-Thoi, T.; Rabczuk, T. (International journal of impact engineering, 2016)
In this study, a three-dimensional (3D) non-ordinary state-based peridynamics (NOSB-PD) formulation for thermomechanical brittle and ductile fracture is presented. The Johnson–Cook (JC) constitutive and damage model is used to taken into account plastic hardening, thermal softening and fracture. The formulation is validated by considering two benchmark examples: 1) The Taylor-bar impact and 2) the Kalthoff–Winkler tests. The results show good agreements between the numerical simulations and the experimental results. •A non-ordinary state-based peridynamics is proposed for thermoplasticity.•Adiabatic heating condition is considered.•The Johnson–Cook constitutive and damage model is used.•Taylor-bar impact and Kalthoff–Winkler experimental tests are simulated and validated.